Proposed force majeure clause for construction contracts under prevailing laws - Abu Helw, Amr Mohammad (AUC Knowledge Fountain, 2018)
Force majeure is one of the most critical risks that affects the obligations of the contract parties in the construction industry. The concept of force majeure, basically, is a civil law concept that is found in the civil codes of most civil law jurisdictions, while common law does not recognize such concept with the same wide definition and application. Occurrence of a Force majeure event can dramatically affect the execution of the contract as it hinders a party of the contract, or both parties, from fulfilling its/their obligations for a reason beyond its/their control and expectation. Thus it is vital to have a well drafted force majeure clause in construction contracts to give an excuse to the affected party from further performance of its obligations under the contract until the expiration of the event or, sometimes, to give a right to terminate the contract. The aim of this research is to propose a force majeure clause applicable to all kinds of construction contracts either governed by a civil law or a common law jurisdiction. To achieve that aim, a questionnaire survey is conducted to explore the opinions and past experience of a selected professional group consisting of twenty five professionals working in the construction field with contract administration background. Based on the finding of literature review, the survey findings, and on a number of contracts the researcher dealt with during his professional life a model clause is developed. The model clause is then verified by obtaining the opinions of three experts in contracts administration. It is also compared with four mega project contracts in several countries. The results of the comparison indicates that the model clause is comprehensive and can be applied to construction contracts to achieve its intended purpose.